Experience with polyurethane intraurethral stents in aged patients - Tsujimoto, Y (Hinyokika kiyo. Acta urologica Japonica, 1993)
A double Malecot-like 16F, polyurethane intraurethral catheter (IUC) was inserted 39 times in 25 patients between 68 and 91 years old (mean +/- SD: 77.5 +/- 5.5 years). Most of them were unfit for surgery because of severe illness or advanced age. All patients except 1 had either an indwelling catheter or a residual urine volume > 50ml at their first visit. The remaining one suffered from prostatic cancer and complained of pollakisuria and urinary incontinence. His symptoms were controlled well after ICU insertion and anticholinergic therapy. Twenty-nine insertions in 17 patients were considered successful, and the patients with successfully inserted stents voided without residual urine. Nine of 21 patients needed to take anticholinergic drugs. The mean duration of IUC use was 113 days in successful cases. In 9 out of 17 patients with an indwelling IUC for more than 112 days, the catheter became blocked by stones or clots. Therefore, we consider that the device should be changed after 110-120 days. Ten insertions failed for the following reasons: malposition, inappropriate IUC length, spontaneous migration to the bladder in patients with a short prostatic urethra, urinary retention due to underactive detrusor, and total incontinence and bleeding from prostatic cancer